2020
DOI: 10.3389/fphar.2020.00529
|View full text |Cite
|
Sign up to set email alerts
|

Turning Meadow Weeds Into Valuable Species for the Romanian Ethnomedicine While Complying With the Environmentally Friendly Farming Requirements of the European Union’s Common Agricultural Policy

Abstract: The cross-compliance mechanism of the European Union (EU)'s common agricultural policy (CAP) makes the approval of the direct payments to the European farmers subject to compliance with the requirement to maintain the land in good agricultural and environmental condition. One of the obligations of the Romanian land owners and farmers is to avoid the installation of unwanted vegetation on their land plots. This vegetation is represented by some species of herbaceous or woody plants, annual or perennial, that sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…3) [45]. In general, the roots, buds, and seeds of A. lappa have widely been employed in traditional medicine for treatment of hepatitis, hypertension, gout, and inflammatory diseases, also serving as a blood purifier, and they have been used as a remedy for rheumatism, scurvy, venereal disease, and sores, with the leaves being used for the healing of wounds, burns, and gastric ulcers [46][47][48]. Since the roots are traditionally used to treat diseases such as sore throat and infections such as rashes, boils and various skin problems, the seed and fruits are also used for skin conditions, as well as in cold/flu formulae [49].…”
Section: Taxonomy Botanical and Ethnopharmacological Aspectsmentioning
confidence: 99%
“…3) [45]. In general, the roots, buds, and seeds of A. lappa have widely been employed in traditional medicine for treatment of hepatitis, hypertension, gout, and inflammatory diseases, also serving as a blood purifier, and they have been used as a remedy for rheumatism, scurvy, venereal disease, and sores, with the leaves being used for the healing of wounds, burns, and gastric ulcers [46][47][48]. Since the roots are traditionally used to treat diseases such as sore throat and infections such as rashes, boils and various skin problems, the seed and fruits are also used for skin conditions, as well as in cold/flu formulae [49].…”
Section: Taxonomy Botanical and Ethnopharmacological Aspectsmentioning
confidence: 99%
“…For example, medicinal plants from bushes and weeds can grow rapidly and easily dominate re-vegetated areas [3]. Some are traditionally used to treat infectious or non-infectious diseases due to their various activities, such as antihypertensive, antimalarial, anti-inflammatory, anticancer, antioxidant, antibacterial and antifungal [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The global market for herbal products is rapidly expanding and expected to reach 115,000 million US$ in 2020 (Raclariu et al, 2018a) while the trade of medicinal plants will continue to advance with annual growth rates of 15-25% (Booker et al, 2012). This increasing demand for plant-based products has resulted in a proportionally increase of peer-reviewed reports of accidental contamination or intentional, economically motivated adulteration (de Boer et al, 2015;Ichim et al, 2018;Simmler et al, 2018;Grazina et al, 2020;Grosu and Ichim, 2020). A global analysis of nearly 6,000 herbal products sold in 37 countries has revealed that 27% of the products contain undeclared contaminants, substitutes, or filler species (Ichim, 2019).…”
Section: Introductionmentioning
confidence: 99%